(133) فرص ومجالات التعاون بين مصر ومجموعة دول الكومسيا Opportunities and areas of cooperation between Egypt and the COMESA group of countries - محمد محمود رزق; ممدوح الشرقاوي; احمد عبدالوهاب برانية; عبدالقادر دياب; حسام نجاتي; وأخرون (معهد التخطيط القومى؛, 2018)
يونيه 2000.